2012
DOI: 10.1053/j.gastro.2012.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Spleen Stiffness to Evaluate Portal Hypertension and the Presence of Esophageal Varices in Patients With HCV-Related Cirrhosis

Abstract: Measurement of SS can be used for noninvasive assessment and monitoring of PH and to detect EV in patients with hepatitis C virus-induced cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
421
7
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 463 publications
(457 citation statements)
references
References 32 publications
23
421
7
6
Order By: Relevance
“…19 New transient elastography probes (XL probe), as well as new sonoelastography methods, might overcome this limitation of transient elastography, 34 with the added advantage of improving the applicability of measurement of spleen stiffness, which is emerging as a novel noninvasive parameter closely correlating with HVPG and presence of EVs. 35,36 Second, the prevalence of EVs in our population of compensated patients was relatively low, which might represent a bias for the generalizability of our results 37 ; however, the prevalence of varices in the validation cohort was exactly as anticipated. It should also be noted that patients included in the training set and in the validation set differed in a number of characteristics; however, the similar results obtained by applying our models in the validation set further confirms the robustness of our findings.…”
Section: Clinical Livermentioning
confidence: 76%
“…19 New transient elastography probes (XL probe), as well as new sonoelastography methods, might overcome this limitation of transient elastography, 34 with the added advantage of improving the applicability of measurement of spleen stiffness, which is emerging as a novel noninvasive parameter closely correlating with HVPG and presence of EVs. 35,36 Second, the prevalence of EVs in our population of compensated patients was relatively low, which might represent a bias for the generalizability of our results 37 ; however, the prevalence of varices in the validation cohort was exactly as anticipated. It should also be noted that patients included in the training set and in the validation set differed in a number of characteristics; however, the similar results obtained by applying our models in the validation set further confirms the robustness of our findings.…”
Section: Clinical Livermentioning
confidence: 76%
“…Also, Colecchia et al (10) concluded that SSM and LSM were more accurate than other non-invasive parameters in identifying patients with EV. In their study, LSM could predict EV with cut-off ≥ 25 with sensitivity 56% and specificity 97%, while SSM could predict EV with cut-off value ≥ 55 with sensitivity 71% and specificity 95%.…”
Section: Discussionmentioning
confidence: 99%
“…The tip of the probe transducer was placed on the skin between the rib bones at the level of the right lobe of the liver. Results were expressed in KiloPascals (kPa) and corresponded to the median of 10 validated measurements (10) . The examination was considered reliable if more than ≥ 10 valid measurements were acquired, the success rate (number of valid acquisitions divided by the number of attempts) was over 60%, and the ratio of the interquartile range to the median of 10 measurements (IQR / M) was less than or equal 0.3 (11) .…”
Section: Liver Stiffness Measurement (Lsm)mentioning
confidence: 99%
“…Spleen stiffness has recently received considerable attention as an indicator of portal hypertension 79 because it can be examined by non-invasive imaging systems such as transient elastrography 80 and acoustic radiation force impulse imaging. 79,81 Some studies also suggest that spleen stiffness could predict the presence of varices [79][80][81] or ascites.…”
Section: Splenomegalymentioning
confidence: 99%
“…79,81 Some studies also suggest that spleen stiffness could predict the presence of varices [79][80][81] or ascites. 82 An experimental model of cirrhosis with portal hypertension has demonstrated that portal pressure positively correlated with the spleen size.…”
Section: Splenomegalymentioning
confidence: 99%